IMPLEMENTASI LAYANAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS “SLOW LEARNER” DI SLB SAMUDRA LAVENDER - Ramzi Al Bani Thariq; Putri Prihandini Agustin; Hesti Wahyu Widayanti; Mahsa Kamilah; Nova Estu Harsiwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Slow learners are children with special educational needs who require learning services tailored to their abilities and characteristics. Their slower learning pace often creates challenges in achieving optimal academic outcomes. This study aimed to analyze the implementation of educational services for slow learner students at Lavender Ocean Special School. The study employed a qualitative approach with a case study design. Research participants were selected through purposive sampling and consisted of classroom teachers who directly handled slow learner students. Data were collected through in-depth interviews and classroom observations, then analyzed using the Miles and Huberman interactive model. Data validity was ensured through technique triangulation by comparing interview and observation results. The findings revealed that slow learner students were grouped according to their ability levels and received learning support through direct instruction, modeling, and individualized assistance. Teachers also utilized contextual approaches and concrete learning media to facilitate students’ understanding. Learning evaluation was conducted through diagnostic, formative, and summative assessments integrated with Individualized Education Programs (IEPs). The main challenges included diverse student abilities within the same classroom, limited learning facilities, and the need for intensive guidance. Collaboration between teachers and parents played a crucial role in addressing these challenges. The study concludes that educational services that are flexible, concrete, and oriented toward individual student needs are essential for supporting the learning success of slow learner students in special education settings. ABSTRAK Anak slow learner memerlukan layanan pendidikan yang disesuaikan dengan kemampuan dan karakteristik belajarnya karena mengalami hambatan dalam memahami materi akademik. Penelitian ini bertujuan untuk menganalisis implementasi layanan pendidikan bagi anak berkebutuhan khusus slow learner di SLB Samudra Lavender. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian adalah guru kelas yang menangani peserta didik slow learner dan dipilih secara purposive sampling. Data dikumpulkan melalui wawancara mendalam dan observasi kelas, kemudian dianalisis menggunakan model Miles dan Huberman melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji dengan triangulasi teknik. Hasil penelitian menunjukkan bahwa layanan pendidikan dilaksanakan melalui pengelompokan peserta didik berdasarkan tingkat kemampuan, penggunaan metode instruksi langsung, modelling, pendampingan individual, serta pemanfaatan media konkret dan pendekatan kontekstual. Evaluasi pembelajaran dilakukan melalui asesmen diagnostik, formatif, dan sumatif yang dipadukan dengan Program Pembelajaran Individual. Kendala yang dihadapi meliputi heterogenitas kemampuan peserta didik, keterbatasan sarana pembelajaran, dan tingginya kebutuhan pendampingan. Untuk mengatasinya, guru menjalin kerja sama dengan orang tua dalam mendukung proses belajar anak. Penelitian ini menyimpulkan bahwa layanan pendidikan yang fleksibel, konkret, dan berorientasi pada kebutuhan individu berperan penting dalam mendukung keberhasilan belajar anak slow learner di SLB.